Enynal/Enynone: A Safe and Practical Carbenoid Precursor - Ma, Jun; Zhang, Li; Zhu, Shifa (Current Organic Chemistry, 2016)
Recently, non-diazo carbene precursors have attracted more and more interest because of the apparent safety reason. As one of the most reliable and useful non-diazo carbenoid precursors, enynal/enynone can give rise to furyl- or pyrylium-carbene, which has be applied in a wide range of carbene-transfer reactions, such as cyclopropanation, C-H and X-H insertion, 1,3-dipolar cycloaddition and ylide formation reaction.
Keywords: Carbene